2020
DOI: 10.1038/s42004-020-00345-6
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and thermodynamic studies of chromic overcrowded fluorenylidene-acridanes with modified fluorene moieties

Abstract: Chromic materials, an important class of stimuli-responsive materials, have aroused extensive attention in recent years. Normally, their color is based on changes in morphology. Few examples of chromic material based on conformational isomerization, such as in overcrowded alkenes, have been reported previously. Furthemore, experimental thermodynamic studies of overcrowded bistricyclic aromatic enes have not been carried out to our knowledge. Here, we show that N-phenyl-substituted fluorenylidene-acridanes, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…17 Single crystal analysis for 1 also was done and indicated that the folded conformer existed in the crystalline state. 19 In the present work, to support these previous reports, we studied why this transformation was induced by mechanical pressure by performing DFT calculations with a B3LYP/6-31G(d) method/basis set using the Gaus-sian09 package. Monomers and dimers of 1 in the folded and twisted conformers were calculated (Fig.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…17 Single crystal analysis for 1 also was done and indicated that the folded conformer existed in the crystalline state. 19 In the present work, to support these previous reports, we studied why this transformation was induced by mechanical pressure by performing DFT calculations with a B3LYP/6-31G(d) method/basis set using the Gaus-sian09 package. Monomers and dimers of 1 in the folded and twisted conformers were calculated (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…From among FA derivatives, we selected dimethoxy fluorenylidene acridane (1) [17][18][19] because the electron-donating dimethoxy groups on the acceptor part inhibit charge transfer, which occurs only in the twisted conformer. Therefore, dimethoxy groups cause the molecule to adopt the folded conformation as the initial state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to those of other OCEs, FAE 1 and 2 display mechanochromic behavior in the solid state [4f–h,13] . For example, grinding an orange crystal of FAE 1 or yellow crystal of FAE 2 causes the colors to change to dark red and orange color, respectively (Figures 9 and S22).…”
Section: Resultsmentioning
confidence: 73%
“…There are two approaches to weakening the bonding interaction: stretching the bond and twisting the bond (Figure a). , Quinoidal and cumulenic biradicals can be regarded as the result of the bond-stretching operation, although the scaffold is extended. The bond-twisting operation has been attained by enforcing the twisted structure through steric repulsion between bulky substituents at both ends of the ethylene moiety. These ethylenes with bulky substituents are termed overcrowded ethylenes and are known for structures with significantly twisted and elongated CC bonds. However, only a few reports have been published on their biradicaloid behavior. , …”
mentioning
confidence: 99%